Global Changes and its Impact on Human Health - Adhikari, Rajdevi (Journal of Nursing Education of Nepal, 2011)
In the past, the earth’s climate has altered following natural causes but at the present the changes have accelerated as a result of human behavior. Human activities like industrialization and population growth directly affect the earth’s climate. Collectively these changes endanger health and future prospects for many other living creatures. Global warming and stratospheric ozone depletion have attracted the most attention, but other changes go beyond these two processes. Climate change contributes to the global burden of diseases, and this contribution is expected to grow in future. A lot of attention has been given to the impact of climate change on our environment, ecosystems and on various plant and animal species. We as human can make small but significant contributions towards preventing and reducing effects of climate change simply by making a few changes in our daily lives.